BEN JONSON’S THE ALCHEMIST, AS A SOCIAL HISTORY - Modupe Elizabeth, Olaniyan (European Scientific Journal, ESJ, 2014)
Drama has been perceived in multi-faceted ways. On a general note, it has been viewed as the reflection of life; the society, to be precise. Thus, any literary work is a by-product of the society where it is written. This study focuses on the play-text as a reflection of the social history of a particular society (London), at a particular period in time(1610), using Ben Jonson’s The Alchemist as our main paradigm. It also examines Jonson’s central themes and characters, as well as taking into consideration, the picture of some outstanding phases of his contemporary life and estimating their values as a contribution to the knowledge and understanding of his time; such subjects as the influence of the Court, Puritanism and the inter-relationship of the classes. The problem has been two-fold; to determine as accurately as possible, Jonson’s view of the time in which he lived and to show how that time shines through his pages, coloured by that view. It is believed that the intellectual perspective of this study has been rightly chosen, hence ,it is expected that the resulting picture of contemporary life, drama and society, will add to the interpretation of the past, and help to widen the horizon of human experiences